PENERAPAN BALANCED SCORECARD SEBAGAI PENGUKUR KINERJA MANAJEMEN PADA KOPERASI WARIS SURAKARTA - Magdalena Nany; Lyna Raharjo; Kurniawan Kurniawan (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
The objective ofthis research was to measure management's performance by applying balanced scorecard. Balanced scorecard is a contemporary management tool used to upgrade organization's capability by multiplying financial performance. Balanced scorecard has 4 perspectives. These perspectives are financial perspective, customer perspective, process intern business perspective and learning and growth perspective. Data were collected by questionnaire and interview. Ninety nine customers and 25 employees ofW ARIS Cooperation were taken as samples. The results obtained from applying balanced scorecard were: (1) Financial perspective, ROI tends to increase, but revenue growth tends to decrease; (2) Customer perspective, patients' retention tends to increase, patients' acquisition tends to decrease, and patients have not satisfied enough with WARIS Coop• eration; (3) Process intern business perspective, cooperation's productivity tends to increase; (4) Learning and growth perspective, employees' retention tends to decrease, but employees' produc• tivity tends to decrease and employees have not satisfied enough with WARIS Cooperation.